Coastal Children’s Literacy within the Social Ecology of ‎Fishing Communities: A Social Capital-Based Mixed-Method ‎Analysis - Rivai Mana; M. Darwis Nur Tinri (Yayasan Darussalam Bengkulu, 2026)
This study examines coastal children’s literacy within the social ecology of fishing communities through a social capital-based mixed-method approach. Literacy in coastal areas is shaped not only by classroom instruction, but also by family relationships, livelihood routines, school-community interaction, access to reading materials, and institutional support. Using an explanatory sequential mixed-method design, the quantitative phase involved 120 upper-grade elementary students living in coastal settlements, while the qualitative phase involved interviews with 15 parents or guardians from fishing-community households. Quantitative data were collected through a coastal children’s literacy test and a social capital questionnaire measuring bonding, bridging, and linking social capital. Qualitative data were obtained through semi-structured interviews and analyzed thematically. The findings show that most children were at a moderate literacy level. Bonding social capital emerged as the strongest predictor of literacy, followed by bridging and linking social capital. Children with better access to reading materials at home demonstrated higher literacy scores. Interview data revealed that parents had strong educational aspirations, yet their support was constrained by fishing work schedules, fatigue, limited academic confidence, and scarce reading resources. Schools functioned as key literacy bridges, whereas institutional support remained weak due to limited village reading programs and community literacy infrastructure. The study concludes that strengthening coastal children’s literacy requires integrated family, school, community, and institutional collaboration.